Estimating treatment coverage for people with substance use disorders: an analysis of data from the World Mental Health Surveys. Issue 3 (21st September 2017) - Degenhardt, Louisa; Glantz, Meyer; Evans‐Lacko, Sara; Sadikova, Ekaterina; Sampson, Nancy; Thornicroft, Graham; Aguilar‐Gaxiola, Sergio; Al‐Hamzawi, Ali; Alonso, Jordi; Helena Andrade, Laura; Bruffaerts, Ronny; Bunting, Brendan; et al.
Abstract : Substance use is a major cause of disability globally. This has been recognized in the recent United Nations Sustainable Development Goals (SDGs), in which treatment coverage for substance use disorders is identified as one of the indicators. There have been no estimates of this treatment coverage cross‐nationally, making it difficult to know what is the baseline for that SDG target. Here we report data from the World Health Organization (WHO)'s World Mental Health Surveys (WMHS), based on representative community household surveys in 26 countries. We assessed the 12‐month prevalence of substance use disorders (alcohol or drug abuse/dependence); the proportion of people with these disorders who were aware that they needed treatment and who wished to receive care; the proportion of those seeking care who received it; and the proportion of such treatment that met minimal standards for treatment quality ("minimally adequate treatment"). Among the 70, 880 participants, 2.6% met 12‐month criteria for substance use disorders; the prevalence was higher in upper‐middle income (3.3%) than in high‐income (2.6%) and low/lower‐middle income (2.0%) countries. Overall, 39.1% of those with 12‐month substance use disorders recognized a treatment need; this recognition was more common in high‐income (43.1%) than in upper‐middle (35.6%) and low/lower‐middle income (31.5%) countries. Among those who recognized treatment need, 61.3% made at least one visit to a service provider, and 29.5% of the latter received minimally adequate treatment exposure (35.3% in high, 20.3% in upper‐middle, and 8.6% in low/lower‐middle income countries). Overall, only 7.1% of those with past‐year substance use disorders received minimally adequate treatment: 10.3% in high income, 4.3% in upper‐middle income and 1.0% in low/lower‐middle income countries. These data suggest that only a small minority of people with substance use disorders receive even minimally adequate treatment. At least three barriers are involved: awareness/perceived treatment need, accessing treatment once a need is recognized, and compliance (on the part of both provider and client) to obtain adequate treatment. Various factors are likely to be involved in each of these three barriers, all of which need to be addressed to improve treatment coverage of substance use disorders. These data provide a baseline for the global monitoring of progress of treatment coverage for these disorders as an indicator within the SDGs.